Embedding Identity and How Clinical Teachers Reconcile Their Multiple Professional Identities to Meet Overlapping Demands at Work. Issue 4 (8th August 2022) - Ortiz-Paredes, David; Rodríguez, Charo; Nugus, Peter; Carver, Tamara; Risør, Torsten
Abstract: Phenomenon: Clinical teachers perform overlapping tasks in education and patient care. They are therefore expected to juggle many professional identities such as educator and clinician. Yet little is known about how clinical teachers negotiate their professional identities. The present research examined the lived experiences of clinical teachers as they manage and make sense of their professional identities in the context of a faculty development program. Approach: This study adopted interpretative phenomenological analysis, which is an idiographic and inductive methodological approach that enables an in-depth examination of how people conceptualize their personal and social worlds. In-depth semi-structured individual interviews were conducted with six purposively sampled Brazilian clinical teachers who were attending a faculty development program. Each participant's lived experience was analyzed independently. Then, these individual analyses were compared against each other to identify convergence and divergence. Findings: Participants recognized one identity, which was labeled as embedding identity, containing other identities and roles. Participants integrated their professional identities in agreement with their personal identities, values, and beliefs, striving thus for identity consonance. Participants understood their craft as a relational process by which they wove themselves into their context and entangled their experience with that of others. They, however, diverged when recognizing who their peers were; whereas some named a single professional group (i.e., family physicians), others had a more comprehensive view and considered as peers healthcare professionals, students, and even patients. Finally, participants identified time constraints and lower prestige of family medicine as a medical discipline vis-à-vis other specialties as challenges posed by their contexts. Insights: Clinical teachers have multifaceted identities, to which they give a sense, manage, and integrate into their daily practice. Participants recognized an embedding identity and looked for common points between the identities it contained, which allowed them to meaningfully reconcile the different demands from their overlapping professional identities. Thus, this research introduces the notion of embedding identity as a strategy to make sense of many professional identities. Variability in the embedding identities depicted in this investigation suggests the fluid and contextualized character of professional identity development. How participants saw themselves also influenced how they behaved and interacted with others accordingly. Understanding clinical teacher identity development enriches current perspectives of what it is like to be one of these medical professionals. Faculty development programs ought to consider these perspectives to better support clinical teachers in meeting the overlapping demands in education and patient care.